Strategi Pengembangan Umkm Sweet pastry Berbasis Prinsip Ekonomi Syariah dalam Meningkatkan Ekonomi Lokal : Studi Kasus di Betungan Kota Bengkulu - Reva Agustia; Al Yesi Fitri Rahayu; Uswatun Hasanah (Dharma Ekonomi, 2026)
This study explores the development strategies of sweet pastry Micro, Small, and Medium Enterprises (MSMEs) based on Islamic economic principles in improving the local economy in Betungan, Bengkulu City. MSMEs play a crucial role in supporting economic growth and creating employment opportunities, particularly in the culinary sector, which has experienced significant expansion in recent years. In Betungan, sweet pastry businesses have shown promising potential; however, their development is still hindered by several challenges, including limited capital, low product innovation, and less effective marketing practices. This research employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation at Jl. Ar-Rahman, Sepakat 7, Betungan, Selebar District, Bengkulu City. The study also considers the application of Islamic business values, emphasizing ethical conduct such as honesty, fairness, accountability, and the avoidance of riba and uncertainty in transactions. The findings indicate that the sustainability and competitiveness of sweet pastry MSMEs can be enhanced through several key strategies, including continuous product innovation, improving product quality, optimizing digital marketing, and strengthening business networks. In addition, integrating Islamic principles into business operations helps build consumer trust and ensures ethical business practices. Overall, these strategies not only improve business performance but also contribute to strengthening the local economy and community welfare.